Spirituality in the Black Arts Movement - Bouallegue, Nadjiba (Afrika Tanulmányok / Hungarian Journal of African Studies, 2024)
The article investigates the significance of spirituality in the works of the Black Arts Movement poets. By examining the poetry of Amiri Baraka and Maya Angelou, the study uncovers the various facets of spirituality that African Americans embrace, including “Africanized” Christianity, jazz poetry, and Islam. The article aims to show if spirituality is merely a way to celebrate cultural diversity or a vehicle for social change. It draws on Gilles Deleuze and Félix Guattari’s theory of minor literature to demonstrate that the Black Arts Movement is a minor literature, whereby cultural markers such as spirituality are politicized. Because spirituality endows the Black Arts Movement with a political value and a collective enunciation, this movement becomes a revolutionary force that aims to enact social change. This politicized spirituality is symptomatic of a desire to foster a strong, positive bond with Africa, which is an antidote to the strangeness of mainstream society. The remembrance of the African past through Afrocentric spirituality is a tool for defining and redefining one’s sense of belonging. It is also a quest for an essentially black aesthetic.